Dyslipidaemia management in the cardiac rehabilitation clinic of a tertiary referral centre; analysis of the impact of new ESC guidance on LDL-C target achievement. (11th May 2021) - Mccaughey, C; Ranganathan, D; Murphy, G; Kerins, M; Murphy, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac rehabilitation (CR) programs provide an opportunity to measure low density lipoprotein cholesterol (LDL-C) levels and optimise lipid lowering therapy (LLT) accordingly. New ESC guidelines released in August 2019 recommend lower absolute LDL-C target levels and an >50% reduction from baseline in those at the highest risk. Purpose: This study investigated the proportion of those patients who finished CR in 2019 that reached both their absolute and relative reduction in LDL-C levels, before and after the introduction of these new guidelines. We also analysed the choice and appropriateness of LLT. Methods: A retrospective chart review of 163 patients who completed CR in 2019. A database was created containing baseline patient characteristics and LDL-C levels both prior and post CR; as well as the patient's contemporary LLT. Those patients who did not have a previous diagnosis of atherosclerotic cardiovascular disease (ASCVD) were risk stratified as per ESC guidance. Baseline LDL-C levels were recorded, where possible, and otherwise calculated using pre-CR LDL profile with an adjustment made based on the projected effects of their LLT. Results: Mean (SD) patient age was 62 (10) years, 123/163 (75%) were male and 142 (87%) patients had established ASCVD. 90/142 (63%) of very high-risk patients were treated with a high intensity LLT and 5/163 overall (3%) were prescribed ezetimibe. Overall, 96/163 (59%) patients in 2019 met their absolute LDL-C targets; 62% of applicable patients achieved an >50% reduction in LDL-C levels. 104 (64%) of patients were treated in compliance with their contemporary guidelines. Both pre (n = 112) and post (n = 51) September 2019 cohorts were well matched. Fewer patients who were treated under the August 2019 guidelines reached their absolute LDL-C (51% v 63%, p < 0.005) targets; achieved a >50% reduction in LDL-C from baseline (48% vs 61%, p < 0.005), or were compliant with the guidelines for their risk category (43% vs 73%, p < 0.005). Conclusions: Both high intensity statin therapy and ezetimibe are under-prescribed. Fewer patients are meeting the lower absolute LDL-C targets set out in the 2019 ESC guidelines. For those at high risk, determining the reduction in LDL-C from baseline reveals that even those meeting their absolute LDL-C targets may still be undertreated.